2016
DOI: 10.1002/gps.4584
|View full text |Cite
|
Sign up to set email alerts
|

Aging perceptions and self‐efficacy mediate the association between personality traits and depressive symptoms in older adults

Abstract: Our results provide support for interventions aimed at improving self-perceptions related to efficacy and aging in order to reduce depressive symptoms in older adults. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 50 publications
(56 reference statements)
6
40
0
3
Order By: Relevance
“…Consistent with hypotheses, older adults who were more hopeless at baseline were more depressed 6 years later, which was partially explained by having more negative SPA 4 years after baseline. These findings are consistent with prior research that has shown hopelessness to prospectively predict depressive symptoms and SPA to mediate relationships between personality characteristics and depressive symptoms . It is notable that the prospective relationships held over 6 years, even after controlling for concurrent levels of hopelessness, SPA, and depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with hypotheses, older adults who were more hopeless at baseline were more depressed 6 years later, which was partially explained by having more negative SPA 4 years after baseline. These findings are consistent with prior research that has shown hopelessness to prospectively predict depressive symptoms and SPA to mediate relationships between personality characteristics and depressive symptoms . It is notable that the prospective relationships held over 6 years, even after controlling for concurrent levels of hopelessness, SPA, and depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Third, using cross-sectional data, SPA and self-efficacy mediated relationships between neuroticism and extraversion with depressive symptoms; SPA was a much stronger mediator than self-efficacy. 16 Consistent with these findings, models of SPA theorize that personality characteristics are likely to be important antecedents, leading to calls for more research on personality. 1,2 One important personality characteristic that may contribute to SPA involves a person's expectations regarding the future and efforts to achieve desired outcomes (ie, goal pursuits).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations